High-energy heavy ion beam annealed ion-implantation-synthesized SiC nanocrystallites and photoluminescence - Khamsuwan J. (2014)
This work explored a novel way to synthesize silicon carbide (SiC). Carbon ions at tens of keV were first implanted in single crystalline silicon wafers at elevated temperature, followed by irradiation using heavy xenon ion beams at high energy of 4 MeV with fluences of 5 × 1013 and 1 × 1014 ions/cm2 at elevated temperatures to play a role of annealing as an alternative of high-temperature thermal annealing. X-ray diffraction, Raman scattering, infrared spectroscopy were used to characterize formation of SiC. Rutherford backscattering spectrometry was used to analyze changes in the carbon depth profiles. Photoluminescence experiment was operated. The results showed that high-energy heavy ion beam annealing could indeed induce crystallization of SiC, mainly depending on the single ion energy but not on the deposited areal density of the ion beam energy (the product of the ion energy and the fluence). The ion beam synthesized SiC could enhance emission of blue-band photoluminescence. ©2010 IEEE.